The Basis of the Deformation Method for Calculating of Elements from Wood under Cross-Section Bending - Gomon, Svyatoslav; Gomon, Svyatoslav; Gomon, Petro; Shkirenko, Serhiy (International Journal of Engineering and Technology, 2018)
The analysis of Ukrainian and foreign norms in calculating whole and laminated wood for different types of loads has been carried out. It is revealed that the calculation of wooden constructions is carried out by methods of boundary states in an elastic stage of work. The real stages of the stress-strain state of bending elements from wood and their constructions, taking into account the plastic work of the material, are considered. Developed and brought some preconditions for calculating given full diagram of the work of the wood taking into account the descending branch. The basis of the method of calculation of elements from solid and glued wood according to the deformation model, taking into account the growth of deformations in the calculated section, is presented.